Fate of carbofuran in rice-fish model ecosystem -an international study - Jayaraman, J.; Celino, L.P.; Lee, K.H.; Mohamad, R.B.; Suns, J.; Tayaputch, N.; Zhang, Z. (Kluwer Academic Publishers, 1989)
Work done in six nations by seven research groups on Carbofuran metabolism in rice-fish ecosystem is summarized. The following results have been obtained: (a) Soil acts as a sink for the pesticide and there is considerable metabolism in the soil; (b) There is no bioaccumulation/biomagnification by the fish used in the experiments, the residue levels in water being extremely low; and (c) The plants translocate the chemical and even at the time of harvest, the grains show the presence of the pesticide.